Fishermen Conflict and the Resolution for Using Fisheries Resources Utilization at Selayar Islands, South Sulawesi - Andi Adri Arief; Harnita Agusanty; Muhammad Dalvi Mustafa (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2020)
This research aims to analyze the existence of fishermen conflicts in using of fisheries resources and settlement conflict resolution. The method used is qualitative research through grounded research that explores various cases and forms of conflict between fishermen (hulle fishermen communities (migrants) with local fishermen. Data analysis refers to the functional structural theory and conflict theory. The result of the research shows that the fishermen or groups of fishermen with their capture technologies (traditional, semi-traditional, and modern) must compete freely and be competitive to get fishery resources. The orientation and utilization of spatial aspects also be a type of conflict that extends to primordial conflict aspects. Conflict resolution through co-management strategies by involving various stakeholders in conflict resolution. Strategic steps must be an emphasis on conflict resolution shape that adaptive and responsive through systematic analysis for acceleration the resolution of fisherman conflict issues that developed so far. The formation of fishermen institutions conflict management is needed that involves government elements (related institution), community leaders, fishermen representative, NGO, and universities in charge of potential analyzing fishermen conflicts and handling strategy.